The Nutrient Status of Mgazana, a Warm Temperate Mangrove Estuary in the Transkei, Eastern Cape, South Africa - Emmerson, W. (Wetlands ecology and management, 2005)
Mgazana, a rural southern African mangrove system, was visited monthly from August, 1995 to February, 1997 to collect water samples for nutrient analysis. Surface and bottom samples were taken during spring low tide at seven stations along the estuary and the following physico-chemical parameters measured: river flow, temperature, salinity, oxygen, transparency, ammonia, nitrite, nitrate, phosphate, inorganic carbon (IC), organic carbon (OC), total carbon (TC), soluble nitrogen (SN), particulate nitrogen (PN) and total nitrogen (TN). Using correlation matrix analysis and ANOVA, river flow was found to affect estuarine salinity, transparency and stratification, which influenced nutrient dynamics. Significant seasonal (winter and summer) differences were found for temperature, river flow, nitrate, SN, TN, IC and OC. Most nutrients were significantly correlated with river flow showing gradients down the estuary, indicating allochthonous input from the catchment. OC levels within the estuary were high, probably due to autochthonous mangrove leaf-fall processing by the various in-fauna, but high levels measured at the head of the estuary during high river flow suggested additional allochthonous input from coastal forest litter. Conversely, IC was negatively correlated with river flow suggesting that autochthonous faunal and microbial mineralisation of organic matter occurs within creeks, which is then diluted by increased stream-flow. An N:P ratio of 2.7:1 was obtained for this rural mangrove system, which was low compared with Spartina-based East Cape estuaries subject to urban, industrial and agricultural pollution.